M-learning in Teaching ESP: Case Study of Ecology Students - Valeeva, Nailya; Pavlova, Elena B; Zakirova, Yulia L (European journal of contemporary education, 2019)
The paper presents research results on mobile learning of English for specific purposes to ecology students with the help of the Quizlet learning platform. The study was conducted in four stages: the students were surveyed about their mobile devices, and then they underwent an experimental mobile learning process during one term. The next stage was to work with authentic texts, during which the skills developed for reading comprehension of authentic specialized texts were assessed. In order to incorporate subject-specific vocabulary into professional discourse, in-class discussions were organized with students at the same stage of the study. The students were assigned to agree or disagree with the statements, prove their point, make arguments using familiar vocabulary on these topics. Such classroom discussions have shown that the subject-specific vocabulary the students mastered in the process of mobile learning is active. In our opinion, this is a very important result of mobile learning. The students also note that it is now easier for them to make up statements on professional topics and participate in conversations after mobile training. At the final stage, the students were surveyed once again in order to clarify their impressions of mobile learning. The paper shows the students are sufficiently equipped with mobile technologies and highly motivated to m-learning. The objective test results and a high level of accuracy when doing followup activities and final tests indicate that mobile learning has increased the effectiveness of teaching ESP. Mobile devices and, above all, smartphones can form a personalized learning environment which is motivating and challenging at the same time. Employment of m-learning tools in ESP instruction, besides increasing foreign language proficiency, enhances the levels of students' satisfaction and motivation which are crucial for professional foreign language communication throughout life.